2011
DOI: 10.1007/s11434-011-4396-0
|View full text |Cite
|
Sign up to set email alerts
|

High-precision measurement of mercury isotope ratios of atmospheric deposition over the past 150 years recorded in a peat core taken from Hongyuan, Sichuan Province, China

Abstract: High-precision measurement of mercury isotope ratios of atmospheric deposition over the past 150 years recorded in a peat core taken from Hongyuan, Sichuan Province, China High-precision 210 Pb dating technology was applied to a peat core with a time span of about 150 years that was taken from Hongyuan, Sichuan Province, China. The concentrations of total mercury (Hg) and stable isotope compositions of mercury in the peat core were measured using a LUMEX 915 instrument and multi-collector inductively coupled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…As shown in Table 2, coal samples in these regions are characterized by the lower THg and the lowest C S content, which probably indicates less hydrothermal activity imprint. 56 Similar to the modern plants [61][62][63]69 and peat samples, 75,76 the coals in these regions have significant MIF of Hg isotopes with a Δ 199 Hg/Δ 201 Hg ratio of ∼1.0 ( Figure S3, Supporting Information). Hence, we hypothesized that the biogenic Hg may be the dominant source of Hg in coals of these regions and Hg is mainly associated with organic matters.…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“…As shown in Table 2, coal samples in these regions are characterized by the lower THg and the lowest C S content, which probably indicates less hydrothermal activity imprint. 56 Similar to the modern plants [61][62][63]69 and peat samples, 75,76 the coals in these regions have significant MIF of Hg isotopes with a Δ 199 Hg/Δ 201 Hg ratio of ∼1.0 ( Figure S3, Supporting Information). Hence, we hypothesized that the biogenic Hg may be the dominant source of Hg in coals of these regions and Hg is mainly associated with organic matters.…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“…The odd-MIF were reported in a large set of environmental, geological, and biological samples, including atmospheric samples [23-25, 36-39, 42, 49, 50], sediments [49,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], soils [37, [68][69][70], peats [71], rocks [72], coals [24,68,73,74], mosses and lichens [50, [75][76][77], human hairs [78][79][80], plants [37,50,81], fishes [3,62,78,[80][81][82][83], and even seabirds [53,84]. Blum et al [22] have given a detail description of these data in a recent review article.…”
Section: Mainstream Observation Of Odd-mifmentioning
confidence: 99%
“…2 , previous studies reported large Hg-MIF mainly in the surface of the crust, such as soil 39 40 41 , sediments 42 43 44 , water 45 46 47 , atmosphere 48 49 and biological samples 14 50 51 52 . Sedimentation 42 43 44 , coalification 37 38 and hydrothermal leaching of Hg from source-rocks 20 have been shown unlikely to alter the MIF signature of Hg; the Hg-MIF signature has been observed in coals (∆ 199 Hg: −0.66 to +0.38‰) 37 38 40 53 , peat bogs (∆ 199 Hg: −0.50 to +0.22‰) 54 55 , and black shales 56 . Although no ∆ 199 Hg data were reported, ∆ 201 Hg values in sedimentary rocks (−0.10 to +0.28‰) have shown larger Hg-MIF compared to the metamorphic rocks (−0.06 to +0.03‰) and volcanic rocks (−0.09 to +0.05‰) in California Coast Ranges, USA 4 .…”
Section: Use Of Hg-mif To Trace Metal Sources In Different Types Of Zmentioning
confidence: 99%